Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Di Kantor Pusat Radio Republik Indonesia (RRI Jakarta - Putera, Adhitya Ibanda; Rasenda, Rasenda; Wiyana, Hari; Asih, Afifah Tri (Yayasan Bina Internusa Mabarindo, 2024)
In the era of globalization and rapid technological advancement, human resources (HR) have become a key factor in a company's success. This study focuses on the impact of compensation and work environment on employee performance, with job satisfaction as an intervening variable at Radio Republik Indonesia (RRI) Jakarta, a public broadcasting institution that must adapt quickly to remain relevant and competitive. The study employs Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to analyze data from 150 respondents. The findings reveal that: (1) Compensation has a positive and significant effect on employee performance. (2) Work environment does not have a significant impact on employee performance. (3) Compensation has a positive and significant effect on job satisfaction. (4) Work environment also has a positive and significant effect on job satisfaction. (5) Job satisfaction has a positive and significant effect on employee performance. (6) Job satisfaction acts as a mediator between compensation and employee performance. (7) Job satisfaction also mediates the relationship between work environment and employee performance. These findings emphasize that while both compensation and work environment positively influence job satisfaction, only compensation has a direct and significant impact on employee performance. Job satisfaction plays a crucial mediating role in this relationship. The study suggests evaluating and adjusting compensation schemes and improving the work environment to optimize employee performance at RRI Jakarta.